Nonlinear approach to study the acute effects of static and dynamic stretching on local dynamic stability in lower extremity joint kinematics and muscular activity during pedalling - Abbasi, Ali; Zamanian, Mehdi; Svoboda, Zdeněk (Human movement science, 2019)
Researchers have reported contradictory results on the effect of static and dynamic stretching on subsequent performance. Due to the importance of performance through static and dynamic stretching, the aim of this study is to investigate the acute effects of static and dynamic stretching protocols on local dynamic stability in lower extremity joint kinematics and muscular activities during pedalling using a nonlinear dynamics approach. Using a randomised crossover trial design, fifteen active males participated voluntarily in this research (mass: 69.02 ± 10.52 kg, height: 174.00 ± 6.74 cm, and age: 21.20 ± 1.47 years) and completed a pedalling trial in situations of without stretching (WS), after static (SS), and dynamic stretching (DS) of lower extremity. The lower extremity joint angles in the sagittal plane and the electrical activity of soleus, gastrocnemius medialis, tibialis anterior, vastus medialis, biceps femoris, and rectus femoris muscles were collected during 30 pedalling cycles at 70 rates per minute. The results of the repeated measure ANOVA indicated that the knee and ankle angle largest LyE was significantly lower in DS compared to WS and SS. The largest LyE in muscle activity is also significantly lower for all the muscles after DS compared to WS and SS (P ≤ 0.05). Regarding the positive effects of DS on the joints and the muscle activity local dynamic stability, it is suggested to use DS than SS in the warm-up program before repetitive activities like pedalling.
Keywords: Dynamic stretching; Local dynamic stability; Static stretching; Largest Lyapunov exponent; Pedalling